Efficacy and Safety of Sodium Tanshinone IIA Sulfonate Injection on Hypertensive Nephropathy: A Systematic Review and Meta-Analysis - Xu, Junyao; Zhang, Chenghua; Shi, Xiaoqing; Li, Jie; Liu, Ming; Jiang, Weimin; Fang, Zhuyuan (Frontiers in Pharmacology, 2019)
Background: Sodium tanshinone IIA sulfonate (STS) injection, the extractive of traditional Chinese medicine Danshen, is supposed to be a supplementary treatment in hypertensive nephropathy. Objectives: To evaluate the efficacy and safety of STS in treatment of hypertensive nephropathy. Methods: We systematically searched China National Knowledge Infrastructure (CNKI), Chinese Scientific Journals Database (VIP), Wan-fang database, Chinese Biomedicine Database (CBM), PubMed, Embase, Web of Science, and Cochrane Library from their inception to December 2018. All studies were screened by two reviewers according to the inclusion and exclusion criteria independently. The Cochrane Collaboration's risk tool was used to assess the methodological quality of the included studies. Reviewer Manager 5.3 was employed for statistical analysis. Results: Sixteen trials involving 1,696 patients were included. The meta-analysis results indicated a combination of STS and angiotensin receptor blockers (ARBs) was more effective than ARB monotherapy in modulating hypertensive nephropathy, as represented by improved estimated glomerular filtration rate (eGFR) [mean difference (MD) = 6.87, 95% CI (4.47, 9.28), P < 0.00001] and reduced 24 h urinary protein [MD = −0.23, 95% CI (−0.27, −0.19), P < 0.00001], serum creatinine (SCr) [MD = −21.74, 95% CI (−24.11, −19.38), P < 0.00001], cystatin-C [MD = −0.16, 95% CI (−0.24, −0.07), P = 0.0003], urinary immunoglobulin G (IgG) [MD = −0.85, 95% CI (−1.11, −0.59), P < 0.00001], and urinary transferrin [MD = −0.61, 95% CI (−1.04, −0.17), P = 0.007]. In addition, the combination therapy had better control in systolic blood pressure (SBP) [MD = −6.53, 95% CI (−8.19, −4.87), P < 0.00001] and diastolic blood pressure (DBP) [MD = −4.14, 95% CI (−5.69, −2.59), P < 0.00001]. Only three trials reported adverse events, and no adverse drug reactions were observed. Conclusions: STS combined with ARBs had a stronger effect on improving renal function in patients with primary hypertensive nephropathy than ARB monotherapy. The combination therapy also provided auxiliary hypotensive effects. Further large-scale, multicenter, and rigorously designed randomized controlled trials (RCTs) should be conducted to confirm our findings.